Effect of Chilled Air Coolant on Surface Roughness and Tool Wear When Machining 2205 Duplex Stainless Steel - Liew, P. J.; Hashim, U. S.; Abd Rahman, M. N. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Cutting fluid is important to enhance machinability. However, conventional cutting fluid is uneconomical and hazardous to environment and health. Thus, non conventional coolant method is studied in order to overcome these problems. In this study, the effect of chilled air coolant on surface roughness and tool wear when machining 2205 duplex stainless steel is investigated. The compressed air is chilled by using vortex tube. Cold air and hot air is produced by means of vortex tube from the source of compressed air. This study also investigated the comparison of machining performance between conventional flood coolant and chilled air coolant. The tests were conducted on a conventional turning machine with TiAlN coated carbide tools and the constant parameters were feed rate, cutting depth, and cutting speed. Surface roughness and tool wear were measured after each run and the results were analysed. The experiment results showed that chilled air coolant gave better surface finish compared to conventional flood coolant. However, tool life was better when using conventional flood coolant compared to chilled air coolant. For both coolant method, the result showed decreasing trend for surface roughness and tool wear values when the temperature of chilled air coolant decreased.